Challenges And Obstacles Of The Implementation Of Sustainable Development Construction Building Construction Projects In Indonesia (International Conference of Graduate School on Sustainability (ICGSS), 2020)
This research uses the Literature study method, which is an analysis that aims to describe the content of the materials based on the collection of informations obtained from various scientific articles related to the application of the concept of sustainable development construction as well as finding solutions to obstacles and challenges in building the construction project process  buildings in Indonesia. The obstacles and challenges faced by contractors in implementing Green Construction as followed: 1)  Technology adaptation, 2). The active role of the project owner, 3). Lack of regulations 4). Public Education, 5). Government financial support. The process of implementing Green Building in the field needs to pay attention to the process are planned, designed, executed, controlled and evaluated. Conducting education for construction actors in the practical sector through internal collaboration mechanisms between service providers based on company qualifications.  Socialization to the public is needed  especially  saving water, energy, not using hazardous substances such as mercury, styrofoam which are not environmentally friendly. Thus, in achieving Green Construction  is  accordance with the principle of sustainability, awareness of the community  and contractors is needed in choosing materials friendly environment   in the concept of implementing Sustainable Development Construction in buildings in Indonesia. Keywords: building, construction, development, obstacle, sustainable Challenges And Obstacles Of The Implementation Of Sustainable Development Construction Building Construction Projects In Indonesia Anna Priscilla De Lima Program Studi Magister Arsitektur, Universitas Merdeka Malang Indonesia Email: prizciliadelima06@gmail.com Abstract. This research uses the Literature study method, which is an analysis that aims to describe the content of the materials based on the collection of informations obtained from various scientific articles related to the application of the concept of sustainable development construction as well as finding solutions to obstacles and challenges in building the construction project process buildings in Indonesia. The obstacles and challenges faced by contractors in implementing Green Construction as followed: 1) Technology adaptation, 2). The active role of the project owner, 3). Lack of regulations 4). Public Education, 5). Government financial support. The process of implementing Green Building in the field needs to pay attention to the process are planned, designed, executed, controlled and evaluated. Conducting education for construction actors in the practical sector through internal collaboration mechanisms between service providers based on company qualifications. Socialization to the public is needed especially saving water, energy, not using hazardous substances such as mercury, styrofoam which are not environmentally friendly. Thus, in achieving Green Construction is accordance with the principle of sustainability, awareness of the community and contractors is needed in choosing materials friendly environment in the concept of implementing Sustainable Development Construction in buildings in Indonesia. Keywords: building, construction, development, obstacle, sustainable